2018
DOI: 10.3892/etm.2018.6923
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rosuvastatin on vascular endothelial functions and inflammatory factors of patients with type 2 diabetes mellitus and coronary heart disease

Abstract: Effects of rosuvastatin on vascular endothelial functions and inflammatory factors of patients with type 2 diabetes mellitus and coronary heart disease were investigated. Eighty patients with type 2 diabetes mellitus and coronary heart disease, who were admitted and treated in Center hospital of Zibo from January 2016 to January 2017, were selected and divided into observation group (n=40) and control group (n=40) by the random number table; symptomatic and supporting therapy, including use of metformin, capto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In this study, patients in the hypoglycemia and hyperglycemia groups had higher levels of FBG, 2 hPG and HbA1c when comparing to their counterparts in the control group, with a lower level of FINS in serum (all P < 0.05), suggesting the damage to the function of pancreas islet, insufficient secretion of insulin, insulin resistance in type II diabetes mellitus patients with CHD, triggering increases in the blood glycemia and glycosylated hemoglobin, which could further deteriorate the functions of vascular endothelium. Ma and Bi (2019) reported that rosuvastatin raises the level of FINS in type II diabetes mellitus patients with CHD, while application of rosuvastatin shows significance in ameliorating the insulin function and resistance. Chen et al (2018) demonstrated that Telmisartan could better regulate the level of blood glucose and reduce the insulin resistance and inflammation, thus improving the vascular endothelial functions in diabetes mellitus patients with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, patients in the hypoglycemia and hyperglycemia groups had higher levels of FBG, 2 hPG and HbA1c when comparing to their counterparts in the control group, with a lower level of FINS in serum (all P < 0.05), suggesting the damage to the function of pancreas islet, insufficient secretion of insulin, insulin resistance in type II diabetes mellitus patients with CHD, triggering increases in the blood glycemia and glycosylated hemoglobin, which could further deteriorate the functions of vascular endothelium. Ma and Bi (2019) reported that rosuvastatin raises the level of FINS in type II diabetes mellitus patients with CHD, while application of rosuvastatin shows significance in ameliorating the insulin function and resistance. Chen et al (2018) demonstrated that Telmisartan could better regulate the level of blood glucose and reduce the insulin resistance and inflammation, thus improving the vascular endothelial functions in diabetes mellitus patients with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical observation experiment to explore the effect of TXL on the coagulation and fibrinolysis function of patients with type 2 diabetes and coronary heart disease (DM-CHD), Ma, T. et al [ 198 ] randomly divided 120 patients with DM-CHD into a conventional treatment group and a conventional treatment plus TXL group, with 60 cases in each group for 2 months. The research results show that TXL can improve the coagulation fibrinolysis function of DM-CHD patients, and its mechanism may be related to the decrease in vWF, F1+2, FIB, PAI-1 levels and the increase in t-PA activity.…”
Section: The Mechanism Of Tongxinluo In Preventing and Treating Cardi...mentioning
confidence: 99%